2017
DOI: 10.18632/oncotarget.22688
|View full text |Cite
|
Sign up to set email alerts
|

The combination of preoperative platelet count and neutrophil lymphocyte ratio as a prognostic indicator in localized renal cell carcinoma

Abstract: IntroductionThe combination of platelet count and neutrophil to lymphocyte ratio (COP-NLR) has been shown to provide prognostic information in several cancers, whereas its prognostic value in renal cell carcinoma (RCC) has not been reported. The objective of the present study was to examine the preoperative prognostic value of the COP-NLR in patients with localized RCC undergoing nephrectomy.Material and MethodsThe record of 268 patients, who underwent nephrectomy due to a diagnosis of RCC at our institute was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…PLT can release growth factors (PLT-derived growth factor, PLT factor, transforming growth factor beta, vascular endothelial growth factor), which may stimulate tumor growth and angiogenesis [16]. The combination of PLT count and NLR has been shown to be an independent prognostic indicator of OS and recurrence-free survival (RFS) for patients with localized RCC [17]. …”
Section: Introductionmentioning
confidence: 99%
“…PLT can release growth factors (PLT-derived growth factor, PLT factor, transforming growth factor beta, vascular endothelial growth factor), which may stimulate tumor growth and angiogenesis [16]. The combination of PLT count and NLR has been shown to be an independent prognostic indicator of OS and recurrence-free survival (RFS) for patients with localized RCC [17]. …”
Section: Introductionmentioning
confidence: 99%
“…In the molecular‐targeted therapy era, the IMDC risk classification is a standard risk‐based stratification . Whereas the IMDC classification includes inflammatory markers, such as neutrophil and platelet count, several studies have suggested that systemic inflammation measured by NLR and CRP also plays a key role in prognosis in mRCC . Recently, the CAR, a novel inflammation‐based prognostic score, has shown outstanding prognostic value in several cancers .…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Whereas the IMDC classification includes inflammatory markers, such as neutrophil and platelet count, several studies have suggested that systemic inflammation measured by NLR and CRP also plays a key role in prognosis in mRCC. [14][15][16] Recently, the CAR, a novel inflammation-based prognostic score, has shown outstanding prognostic value in several cancers. [17][18][19] However, only a few studies investigated the impact of CAR on prognosis in patients with mRCC, and no study compared the effect of CAR with the mGPS on prognosis in mRCC.…”
Section: Introductionmentioning
confidence: 99%
“…46 Recently, the COP-NLR has been described as a prognostic indicator as well. 7, 8, 13 The COP-NLR system was originally developed to combine the inflammatory data from the NLR and information from reactive thrombocytosis in the platelet count. Building on the previous work by Nakayama, this study sought to find out if the COP-NLR was prognostic in a wide variety of HNCs in various stages.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the combination of platelet count to neutrophil-lymphocyte ratio (COP-NLR) has been reported as a prognostic indicator in head and neck cancer 7 and other sites. 8 The study by Nakayama reported only in patients with advanced disease (Stage 3 and Stage 4 disease). Another finding in their paper was that the modified COP-NLR was a better prognostic model than the other COP-NLR models, the 4-group COP-NLR model and the Original COP-NLR model.…”
Section: Introductionmentioning
confidence: 99%